Mathematical and Engineering Aspects of Chemically Reactive Tangent Hyperbolic Nanofluid over a Cone and Plate with Mixed Convection. (13th April 2020) - Bilal, Sardar; Shah, Zahir; Kumam, Poom; Thounthong, Phatiphat
Abstract : Current disquisition is expressed to elucidate the mathematical and engineering aspects of tangent hyperbolic liquid over a cone and plate which has valuable applications in industrial technological instruments such as cone and plate viscometer, spinning column technology, and biomass pyrolysis processing. The role of mixed convection and chemical reaction on physical features of fluid is considered. The attained coupled system is scrutinized by the aid of self-coded shooting method. In order to produce accuracy and refinement in the consequences, the coefficients of Runge–Kutta scheme are obliged. To get complete intellect about the current pagination, the impact of flow controlling variables on pertinent profiles are evaluated in quantitative and qualitative manner. The computations of wall drag force and heat and mass fluxes are presented pictorially and tabularly. From the thorough analysis, it is deduced that surface drag and convective thermal coefficient for cone is more in magnitude compared with those of plate. Similarly, dominance in thermal field is noted for cone compare with that in plate. Increment of velocity profile is revealed with enhancement in mixed convection parameter, whereas contrasting behavior is observed by varying Williamson and magnetic field parameters. Declining aptitude in thermal profile is exhibited against Prandtl number, whereas temperature of fluid mounts by changing the Brownian movement and thermophoresis parameters.